(untitled) (Journal of Fiber Bioengineering and Informatics, 2008)
Research has demonstrated that sensorial clothing comfort is a complex function of material properties, garment design, as well as conditions of use. This paper discusses a modern holistic approach to clothing comfort assessment that is based on a multilevel concept, advancing from the investigation of fabric properties to, ultimately, analysis of complete garment systems in controlled wear trials. It describes the value of the measurements made by advanced instrumented measurement systems when used as part of comprehensive research program designed to explain human response to the wear comfort of functional clothing and materials.